Prospective growth and developmental outcomes in infants born to mothers with multiple sclerosis. (January 2021) - Mahlanza, Tatenda Dawn; Manieri, Maria Claudia; Klawiter, Eric C; Solomon, Andrew J; Lathi, Ellen; Ionete, Carolina; Berriosmorales, Idanis; Severson, Christopher; Stankiewicz, James; Cabot, Ann; Elkort, Michael; Chitnis, Tanuja; et al.
Background: The importance of supporting pregnancy-related decisions in multiple sclerosis (MS) patients has increasingly been recognized and hence the need for prospective data on pregnancy and pediatric outcomes in this patient population. Objective: To assess prospective growth and developmental outcomes of infants born to mothers with multiple sclerosis (IMS). Methods: PREG-MS is a prospective multicenter cohort study in New England, United States. We followed 65 women with MS and their infants with up to 12 months consistent pediatric follow-up. Pediatric, neurologic, and demographic information was obtained via structured telephone interviews and validated with medical records. Results: No differences in infant weights and lengths with World Health Organization (WHO) 50th percentile standards were observed ( p  > 0.05). However, larger head circumference (HC) measurements than WHO standards were reported in cohort infants ( p  < 0.05). There was no association between HC and markers of maternal MS activity, demographic, or social factors. No irreversible pediatric developmental abnormalities were observed. Conclusion: This first prospective study on pediatric anthropometry in IMS suggests a possible increase in HC compared to WHO standards without an increase in irreversible developmental abnormalities. The observations are exploratory and require confirmation with larger prospective studies in diverse groups of MS patients.